USE OF PHYTOTHERAPY IN TREATMENT OF VIRAL HEPATITIS C - Yakubova, Ranokhon; Mamarasulova, Dilfuzakhon; Mamatova, Irodakhonv (Medical science of Uzbekistan, 2025)
Relevance. Viral hepatitis C remains one of the most common liver diseases that requires complex treatment. Due to the limited capabilities of modern medicine in the fight against this disease, the search for additional treatment methods becomes an urgent task. Phytotherapy, as one of the alternative approaches, attracts the attention of researchers due to its availability, low toxicity and potential effectiveness. The introduction of herbal preparations into the complex treatment of viral hepatitis C can help improve clinical outcomes and reduce negative side effects. Despite many studies in the field of herbal medicine associated with various liver diseases, data on the use of plants in the treatment of viral hepatitis C remain limited. Therefore, the purpose of this study is to review and analyze the available literature to assess the potential of herbal medicine as an additional method of treating this disease. The purpose of the study is the use of herbal medicine in the treatment of viral hepatitis C. Materials and methods of research. We observed 128 patients with chronic hepatitis C aged 20 to 60 years, including 46 men and 82 women, who were divided into two groups of 64 people each, randomized by gender and duration of the disease. Patients in the first (main) groups were treated using basic therapy and phytotherapy according to the proposed method, patients in the second group (comparison) received phytotherapy in addition to basic therapy in accordance with the existing prototype method, clinical and laboratory parameters were compared in both groups before the start of treatment, later after the completion of the course of phytotherapy (i.e. after 1 month) and during the period of dispensary examination for 1 year after the completion of phytotherapy in both groups of those examined. Research results. In the comparison group, stable clinical and biochemical remission of chronic viral hepatitis C was achieved after completion of the phytotherapy course in 71.4-4.2% of cases, which is probably less than in the main group (P < 0.05). The use of the proposed method of phytotherapy contributed to an increase in the duration of achieving remission of chronic viral hepatitis. Conclusion. As a result of phytotherapy using the proposed method, the patient achieved complete remission of chronic viral hepatitis C. In general, phytotherapy is a promising direction in the treatment of viral hepatitis, requiring further study and implementation in clinical practice.